2012
DOI: 10.1590/s1413-81232012000300021
|View full text |Cite
|
Sign up to set email alerts
|

Gênero e qualidade de vida percebida: estudo com professores da área de saúde

Abstract: Gênero e qualidade de vida percebida -estudo com professores da área de saúdeGender and perceived quality of life -research with professors from the health areaResumo O rápido processo de mudanças na economia global nos últimos anos e a organização do trabalho configuram as relações de gênero no trabalho docente. Essas transformações têm favorecido a situação desvantajosa da mulher, deixando-a em uma situação de sobrecarga ocupacional. Foram analisadas as condições de trabalho de Professoras do ensino superior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
43

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 12 publications
1
18
0
43
Order By: Relevance
“…Some authors have found that women are more susceptible to stress than men and, therefore, are more prone to have lower levels of quality of life (19) . On the other hand, women express their feelings more openly than men, which can also explain the higher level of stress verified through self-reported data (8,19) . These factors can also explain why, in this study, men were less likely to present signs and symptoms of stress.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have found that women are more susceptible to stress than men and, therefore, are more prone to have lower levels of quality of life (19) . On the other hand, women express their feelings more openly than men, which can also explain the higher level of stress verified through self-reported data (8,19) . These factors can also explain why, in this study, men were less likely to present signs and symptoms of stress.…”
Section: Discussionmentioning
confidence: 99%
“…Em estudo sobre a percepção da qualidade de vida, realizado com docentes da área de saúde, Oliveira et al (2012) identificaram nos relatos a expressão de "ausência de lazer com consequentes distúrbios do sono favorecendo doenças psíquicas; excesso de trabalho; comprometimento da interação social e familiar, com influência sobre a saúde e a qualidade de vida" (Oliveira et al, 2012, p. 741). O trabalho executado por essa categoria contribui para o adoecimento psicossocial e também físico, influenciando a vida familiar e todas as outras esferas de relacionamento, gerando perda da qualidade de vida.…”
Section: Grandes Pressões Do Trabalho () Posso Destacar O Cansaçounclassified
“…Profissionais que acumulam excesso de trabalho, muitas vezes com três jornadas e horários irregulares, podem desencadear um processo de estresse que repercute em sua saúde (BRAGA, PATERNEZ, 2011;OLIVEIRA et al, 2012). Esta rotina pode refletir em sua alimentação, propiciando maus hábitos alimentares (BRAGA, PATERNEZ, 2011).…”
Section: Introductionunclassified